Single nucleotide polymorphism microarrays in the analysis of cancer - Beroukhim, Rameen (Henry Stewart Talks, 2009)
Single nucleotide polymorphisms, Single nucleotide polymorphism arrays, Detecting loss of heterozygosity, Measuring changes in copy-number, Determining allele-specific copy-numbers, Detecting germline cancer risk alleles, Update interview: Microarray vs. sequencing technologies, Update interview: Somatic copy-number alterations, Update interview: Genome topology
Updated at 2020/08/14